2014
DOI: 10.4291/wjgp.v5.i4.487
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary surgical management of rectovaginal fistula in Crohn's disease

Abstract: Rectovaginal fistula is a disastrous complication of Crohn's disease (CD) that is exceedingly difficult to treat. It is a disabling condition that negatively impacts a women's quality of life. Successful management is possible only after accurate and complete assessment of the entire gastrointestinal tract has been performed. Current treatment algorithms range from observation to medical management to the need for surgical intervention. A wide variety of success rates have been reported for all management opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…In recurrent RVF after local procedures, interposition of muscle was developed to introduce healthy, vascularized tissue into the rectovaginal space to allow better healing conditions. In a preliminary experience on eight consecutive cases with recurrent or complex RVF, we observed a success rate after gracilis muscle interposition of 60% . Since our paper, other authors reported also a success rate after gracilis interposition up to 79% .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In recurrent RVF after local procedures, interposition of muscle was developed to introduce healthy, vascularized tissue into the rectovaginal space to allow better healing conditions. In a preliminary experience on eight consecutive cases with recurrent or complex RVF, we observed a success rate after gracilis muscle interposition of 60% . Since our paper, other authors reported also a success rate after gracilis interposition up to 79% .…”
Section: Discussionsupporting
confidence: 61%
“…Among the different surgical procedures used for RVF, tissue interposition methods were intended to interpose normal tissue between vaginal and rectal suture lines and bring well‐vascularized tissue into the rectovaginal space. Several papers have suggested that gracilis muscle interposition is associated with high success fates of around 60−80% and it represents for us the technique of choice after failure of local repair (i.e. rectal or vaginal flap) .…”
Section: Introductionmentioning
confidence: 99%
“…A waiting period of 3 to 6 months is recommended to permit maximal clearance of inflammation and infection. 3 In addition, some authors recommend evaluation of anal wall thickness with ultrasound to ensure it has normalized before definitive repair. 12 At our institution, we typically utilize ultrasound mostly to evaluate the intactness of the anal sphincter.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Local repair can be approached transanally, transvaginally, or transperineally. 3 Simple fistulotomy for low and superficial fistulas with no sphincter involvement may be considered. This will eradicate perianal sepsis; however, patients risk development of a keyhole deformity of the anus and impaired incontinence.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation